Determinants of Mothers’ Choice of Delivery Place at Regina Maris Hospital, Medan - Ramadhani Syafitri Nasution; Nuraini Nuraini; Dina Gokma (PROMOTOR, 2026)
Mothers play an important role in the family, particularly in maintaining their own health and that of their children. However, mothers are also vulnerable to health problems, especially during pregnancy and childbirth. Data from the World Health Organization (WHO) in 2023 show that the global maternal mortality rate remains at 189 per 100,000 live births, with approximately 830 deaths per day, most of which are preventable. Reducing this rate is a target of the Sustainable Development Goals (SDGs) 2030. This study used a quantitative method with a cross-sectional design involving 99 mothers who gave birth at Regina Maris Hospital, Medan, from January to February 2023, using an accidental sampling technique. Data were analyzed using univariate, bivariate, and multivariate methods. The results showed that factors influencing the choice of place of delivery include knowledge, attitudes, beliefs, facilities, and family support, with attitude being the most dominant factor. In conclusion, efforts are needed to improve maternal knowledge and foster positive attitudes, as well as to enhance the active role of hospitals in health promotion.